(untitled) (Bangladesh Journal of Medical Physics, 2018)
Basin type solar stills were made with two types of top cover, transparent PVC sheet and another with glass sheet. A soaked black towel was at the base which was heated through green-house effect and contributed to the water for distillation. Productivity of these two basin type solar stills were studied at different tilt angles of the top transparent cover with ground surface (13o, 23o and 35o). The average amount of distilled water produced increased with the tilt angles for both types of cover materials, that for glass being much higher than that for PVC cover. Bangladesh Journal of Medical Physics Vol.10 No.1 2017 40-46